Sociodemographic factors, social support and risk of postpartum depression (PPD) among postpartum women at Hospital Sultan Haji Ahmad Shah, Temerloh - Mohd Arifin, Siti Roshaidai; Mohamed, Fauzan (2013)
Introduction: In the year 2000, about 200,000 women aged between 18–44 years were discharged with a diagnosis of depression. Postpartum depression (PPD) occurs in more than 15% of all women who given birth worldwide but is believed to be extensively under diagnosed.